A nova indústria nacional de bens e serviços após a flexibilização do monopólio de petróleo - Folkerts, Lívia Karaoglan (2004)
The opening of the Brazilian oil sector approved in 1997 had the objective, among others, of attracting new oil companies to the exploration and production activities. As in general, these already had suppliers at their countries of origin, it was up to public administration to implement mechanisms that would stimulate them to buy goods and services at the local industry. In this way, the opening of the oil sector could promote growth and strengthen the already installed industry, create new ones, and consequently generate the country s growth of income and job creation. The objective of this dissertation is to raise which were the mechanisms implemented and analyze their effectiveness and impacts. The research developed indicated that in the absence of a formal and structured industrial policy for the oil sector, the mechanisms implemented by the regulatory agency aimed to increase the industry s bidding capacity. These mechanisms aimed to assure a greater participation of the Brazilian industry in the purchases of the concessionaires, provide financial support to be applied in its technological capability, develop specialized labor that the sector would demand and promote tributary isonomy to the Brazilian products in regard to the imported ones. The results obtained appoint that the mechanisms implemented reached their objectives, were effective and started a new standard of relationship between the agents of the oil production chain. It is possible to conclude that regulatory instruments can promote growth and strengthen the industry. However, as of 2003, new rules were introduced in regulation which may lead to a possible reversal of the efforts previously endeavored.